2017
DOI: 10.1002/er.3747
|View full text |Cite
|
Sign up to set email alerts
|

Phase change performance assessment of salt mixtures for thermal energy storage material

Abstract: Summary The phase transition performance of the CaCl2 · 6H2O–Ca(NO3)2 · 4H2O composite salt system with nucleating and thickening agents was investigated in this paper. The CaCl2 · 6H2O–Ca(NO3)2 · 4H2O composite salt system was prepared by adding Ca(NO3)2 · 4H2O (12 wt%) to CaCl2 · 6H2O. Different nucleating agents including SrCl2 · 6H2O, SrCO3, BaCl2, BaCO3, Na2B4O7 · 10H2O, H3BO3 and NH4Cl were used to address the problems of phase segregation and supercooling phenomena during the phase change process. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The abstraction of the first hydride from KBH 4 is thought to be the rate‐determining step. [37] All of the borohydride ions react with water, and the degree of conversion depends on the time and the reaction conditions. The fact that the hydrogen yield decreases when the reaction is run at higher concentrations reflects the formation of these complex metaborate intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…The abstraction of the first hydride from KBH 4 is thought to be the rate‐determining step. [37] All of the borohydride ions react with water, and the degree of conversion depends on the time and the reaction conditions. The fact that the hydrogen yield decreases when the reaction is run at higher concentrations reflects the formation of these complex metaborate intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…The eutectic PCMs have the lowest melting temperature in the entire composition range of mixtures of individual phase change materials and the advantages of sharp melting and solidification without any phase segregation, which may provide the desired thermophysical properties for required applications . Most reported eutectics include inorganic–inorganic, especially eutectic hydrated salt (e.g., MgCl 2 ·6H 2 O–Mg­(NO 3 ) 2 ·6H 2 O, CaCl 2 ·6H 2 O–MgCl 2 ·6H 2 O, Na 2 CO 3 ·10H 2 O–Na 2 HPO 4 ·12H 2 O, CaCl 2 ·6H 2 O–Mg­(NO 3 ) 2 ·6H 2 O, CaCl 2 –NH 4 Cl–H 2 O, CaCl 2 ·6H 2 O–Ca­(NO 3 ) 2 ·4H 2 O, etc. ), and organic–organic (e.g., fatty acid eutectic mixtures, fatty alcohol eutectic mixtures, fatty alcohol–fatty acid eutectic mixtures, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…And Xie et al showed that 50 wt% Na 2 SO 4 ·10H 2 O‐50 wt% Na 2 CO 3 ·10H 2 O eutectic system possessed a suitable phase transition temperature (25.41°C) and good melting enthalpy (195.3 kJ·kg −1 ) for building energy storage. Other researchers also prepared binary EHSs with the proper phase transition temperatures for indoor thermal comfort . These above‐mentioned researches about EHS were summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also prepared binary EHSs with the proper phase transition temperatures for indoor thermal comfort. [25][26][27][28] These abovementioned researches about EHS were summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%